THE ROLE OF RELIGIOUS COURT IN ISLAMIC LAW REFORM IN INDONESIA - Amran Suadi (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2019)
Abstract: Law, including Islamic law, will evolve with the changes of time, place, situation and tradition. New social problems grow gradually and pose challenges to Islamic law. Reconstruction and reform are inevitable for Islamic law to respond to the current issues. The Islamic law reforms in Indonesia performed through legal enactment, legal opinion (fatwa), and the Religious Courts decisions. New formula for Islamic law in addressing contemporary issues can be built through three processes: conservation, innovation process, and creation. The Supreme Court of the Republic of Indonesia fully supports the development of Islamic law in Indonesia. The reform of Islamic law by the Supreme Court has been carried out through several instruments, such as the issuance of Perma and SEMA, agreement among justices within the Chamber of the Religious Courts, and creation of jurisprudence.Abstrak: Hukum, termasuk hukum Islam, akan berubah seiring dengan perubahan waktu, tempat, situasi dan tradisi. Masalah sosial baru yang tumbuh secara bertahap tumbuh dan menimbulkan tantangan bagi hukum Islam. Rekonstruksi dan reformasi tidak dapat dihindarkan agar hukum Islam merespons masalah saat ini. Ada tiga tipologi reformasi hukum Islam di Indonesia yang dilakukan melalui pengesahan hukum, pendapat hukum (fatwa), dan keputusan pengadilan dari keputusan Pengadilan Agama. Formula baru untuk hukum Islam dalam menangani masalah kontemporer dapat dibangun berdasarkan tiga proses: proses konservasi, proses inovasi, dan proses penciptaan. Mahkamah Agung Republik Indonesia sepenuhnya mendukung pengembangan hukum Islam di Indonesia. Reformasi hukum Islam oleh Mahkamah Agung telah dilakukan melalui beberapa instrumen, seperti penerbitan Perma dan SEMA, kesepakatan di antara para hakim di Kamar Pengadilan Agama, dan penciptaan yurisprudensi yang diambil dari kasasi.